2004
DOI: 10.1126/science.1094637
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Dependent Regulation of FOXO Transcription Factors by the SIRT1 Deacetylase

Abstract: The Sir2 deacetylase modulates organismal life-span in various species. However, the molecular mechanisms by which Sir2 increases longevity are largely unknown. We show that in mammalian cells, the Sir2 homolog SIRT1 appears to control the cellular response to stress by regulating the FOXO family of Forkhead transcription factors, a family of proteins that function as sensors of the insulin signaling pathway and as regulators of organismal longevity. SIRT1 and the FOXO transcription factor FOXO3 formed a compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

81
2,503
6
18

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,932 publications
(2,656 citation statements)
references
References 26 publications
81
2,503
6
18
Order By: Relevance
“…Several targets of SIRT1 including PGC‐1α and FoxO1/3 have been previously shown to influence mitochondrial biogenesis, antioxidant formation, and inflammation (Brunet, 2004; Lagouge et al, 2006). While we did not observe a statistically significant impact on these pathways in wild‐type mice with aging (data not shown), it is possible that an effect might have been apparent in older animals, as the SOD1 G93A exhibit more severe neuromuscular pathology that is observed during normal aging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several targets of SIRT1 including PGC‐1α and FoxO1/3 have been previously shown to influence mitochondrial biogenesis, antioxidant formation, and inflammation (Brunet, 2004; Lagouge et al, 2006). While we did not observe a statistically significant impact on these pathways in wild‐type mice with aging (data not shown), it is possible that an effect might have been apparent in older animals, as the SOD1 G93A exhibit more severe neuromuscular pathology that is observed during normal aging.…”
Section: Resultsmentioning
confidence: 99%
“…Several targets of SIRT1 including PGC‐1α and FoxO1/3 have been previously shown to influence mitochondrial biogenesis, antioxidant formation, and inflammation (Brunet, 2004; Lagouge et al, 2006). These findings are interesting because mitochondrial dysfunction and the formation of reactive oxygen species are thought to occur in SOD1 mutation carriers as well as patients with C9ORF72 mutations, mutant TDP43, and FUS during ALS pathogenesis (Lopez‐Gonzalez et al, 2016; Onesto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 has been reported to deacetylate the lysine residues of a number of nuclear proteins, such as p53 (Yuan et al., 2011), NF‐κB (Salminen & Kaarniranta, 2009), PGC‐1a (Amat et al., 2009), CBP/p300 (Das, Lucia, Hansen & Tyler, 2009), and forkhead family proteins (Brunet et al., 2004). Several recent studies demonstrated that Sirt1 could inhibit TGF‐β signaling and ameliorate fibrosis (Huang et al., 2014; Kume et al., 2007; Zerr et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed chromatin remodeling factors, such as histone acyl transferases (HAT), or histone deacetylases (HDAC) also can sense redox changes, and thereby lead to changes in transcription. The sirtuin (sirt) family of nicotinamide adenine dinucleotide-dependant (NAD) deacetylases plays an important role in aging and metabolic regulation via control of the FOXO family of Forkhead transcription factors [208]. In response to oxidative stress, sirt1 forms a complex with FOXO3, leading to sirt1-dependent deacetylation of FOXO3, which mediates cell cycle arrest, resistance to oxidative stress, and inhibition of cell death [208].…”
Section: Redox Regulation Of Transcription Factorsmentioning
confidence: 99%